The level of awareness on social marketing through recycling among students in public universities at Kota Kinabalu, Sabah / Silla Nasip - Nasip, Silla (2014)
Social marketing is a systematic procedure that uses commercial marketing strategies to create the awareness among students. Social marketing activities include setting measurable goals, conducting research about target audiences and developing umque promotional tools for different target audiences. As for this research which conducted among publics universities students m Kota Kinabalu the researcher focus on the objective of this research in order to determine the relationship by using the correlation coefficient analysis that using the SPSS Data. The first objective to determine is to identify the recycling awareness through the social marketing for recycling among public universities students. Second objective is to determine the barriers to recycling toward the social marketing for recycling among public university. The respondent of this researcher from UITM Sabah and UMS students by only distribute the questionnaire randomly on their campus. The researcher collect 175 respondent for this research and using the descriptive and correlation to find the finding of the research whether the objective is achieve or not.